KAJIAN HIDROGEOLOGI UNTUK IDENTIFIKASI ZONA POTENSI SUMBER AIR BERBASIS PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS (SIG) DI WILAYAH KECAMATAN CIPATAT, KABUPATEN BANDUNG BARAT, JAWA BARAT - Adang Saputra; Ade Djumarma; Dadan Wildan; Murni Sulastri; Syahadun . (JURNAL GEOGRAFI, 2023)
Groundwater is the water contained in bedrock or regolith, it can also be said to flow naturally to the surface of the soil through jets or seepage. Groundwater has an important role especially for human needs. The research area is administratively located in Cipatat District, West Bandung Regency. Geographically it is located at 6°46'4.84" LS – 6°53'54.30" LS and 107°18'7.44' E – 107°28'53.23" E. The development of the Cipatat area in industrial, service, trade and residential activities can affect the use of groundwater and will continue to increase. The purpose of this study was to identify the potential of water resources using remote sensing methods supported by Geographic Information Systems (GIS), data processing using secondary data and conducting field checks. Satellite image processing classifies Cipatat land class images divided into 4 types of land, from low to high pixel values, namely water body distribution land, ground cover vegetation, plantation vegetation and grasses, as well as forest vegetation, dry fields, and rocky soils. The results of data processing showed that the water critical areas in the study area had a percentage of 3-10% in Bojongheulang, Cipageran, Cirawemekar Mandala sari dan Rajamandala and safe areas with a percentage of 11-51% in Campaka Mekar, Ciburuy, Cihea, Cipatat, Gunung Masigit dan Padalarang. Based on the correlation test of the distribution area of ​​Cipatat and its surrounding vegetation with the distribution area of ​​groundwater, it shows a strong relationship and influences each other. Field checks were carried out in the North and South Cibatat areas.